Exploring the Effects of Adult and Community Education and Training on Economic Development of Women, in South Africa - Tawiah, Sampson (European Scientific Journal, ESJ, 2017)
In South Africa, Adult and Community Education and Training (ACET) is established to cater for the educationally disadvantaged individuals, especially rural women, hence, ACET programmes are running in the country nationally. One of the aims of ACET is to open economic opportunities for women; however, the majority of rural women are still performing poorly economically. This empirical study aimed to explore the effect of ACET on the economic development of women in the Lusikisiki district of South Africa. A qualitative approach in the form of a case study design was used for the study to help the researcher relate to the real life circumstances of the women. Purposive sampling was used to select 35 participants from a population of 115. The participants were selected because they had wealth of information and could explain better the phenomenon under study. Data collection instruments used were face to face individual interviews which were audio recorded with the consent of participants. The major findings of the investigation include the following: inadequate learning resources available to women; inadequate skills development programmes provided and skeptical perception of the economic benefit of ACET to women. The study suggested that the programmes of ACET should be restructured and skills driven to meet the needs of women, especially in rural communities.